Measured Fishing in The North Sea of Java: For Biodiversity Protection or Fishers’ Welfare? - Yusliwidaka, Arnanda; Gunawan, Tri Agus; Pembayun, Jaduk Gilang; Arisa, Frista; Rihardi, Satrio Ageng; Akhni, Ghaziah Nurika (PROGRAM STUDI MAGISTER HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO, 2026)
Indonesia has established and implemented a measured fishing policy in the maritime and fisheries sectors. The aim of this policy is to ensure the sustainability of marine resources, which are a vital source of livelihood for the community, particularly fishers. In practice, however, some fishermen still fail to comply with the regulations due to concerns about their livelihoods, particularly with regard to the use of prohibited fishing gear. This study aims to analyse the implementation of Indonesia's measured fishing policy, focusing on the North Java Sea within the Pati and Lamongan regions. The research employs an empirical legal research method with a regulatory and conceptual approach. The findings of the research indicate that limitations in human resources and infrastructure still exist in the implementation of the measured fishing policy. Insufficient human resources impact monitoring functions, while infrastructure-related issues pertain to the adequacy of equipment for conducting patrols, which are also part of the policy’s monitoring implementation. This study concludes that, despite limitations in human resources and infrastructure affecting the monitoring process, the implementation of measured fishing in the North Java Sea, particularly in the Pati and Lamongan regions, has been carried out optimally.